Two‐year‐supervised resistance training prevented diabetes incidence in people with prediabetes: A randomised control trial. Issue 5 (5th March 2019) - Dai, Xia; Zhai, Lu; Chen, Qingyun; Miller, Joshua D.; Lu, Lirong; Hsue, Cunyi; Liu, Lin; Yuan, Xiaodan; Wei, Wei; Ma, Xiaojun; Fang, Zhaohui; Zhao, Wenpiao; et al.
Abstract: Aim: The purpose of this study is to explore the long‐term effects of aerobic training (AT), resistance training (RT), and combined training (AT + RT) on the prevention of T2D incidence in patients with prediabetes. Materials and methods: In this randomised controlled trial, people with prediabetes (fasting glucose ≥5.6 and <7.0 mmol/L and/or 2‐h glucose ≥7.8 and <11.1 mmol/L on the 75‐g oral glucose tolerance test and/or haemoglobin A1c ≥5.7% and <6.4%) were randomly assigned to the control group, AT group, RT group, or AT + RT group. Supervised exercise programmes, including AT, RT, and AT + RT, were completed for 60 minutes per day, three non‐consecutive days per week for 24 months. The primary outcome was the incidence of T2D; secondary outcomes were blood glucose and lipid levels, including total cholesterol (TC) and standard 2‐hour oral glucose tolerance (2hPG). Results: A total of 137 (80%) subjects with a mean age of 59 years (45 men, 92 women) entered the final analysis. After 24 months of intervention, the incidences of T2D adjusted by sex and age were significantly decreased by 74% (95% CI, 38‐89), 65% (95% CI, 21‐85), and 72% (95% CI, 36‐87) in the AT + RT, RT, and AT groups compared with the control group (HR: AT + RT 0.26 [95% CI, 0.11‐0.62], RT 0.35 [95% CI, 0.15‐0.79], and AT 0.28 [95% CI, 0.13‐0.64]). The cumulative T2D incidences were significantly lower in the AT + RT, RT, and AT groups than in the control group (21%, 26%, and 22% vs 69%). The blood glucose and lipid profiles improved more in the AT, RT, and AT + RT groups than in the control group. Conclusion: RT and RT plus AT were as effective as isolated AT in preventing progression to T2D.